Evidence that subclinical somatoform dissociation is not characterised by heightened awareness of proprioceptive signals - Ratcliffe, Natasha; Newport, Roger (Taylor & Francis, 2016)
Introduction: It has been suggested that abnormal perceptual processing and somatosensory amplification may be contributory factors to somatoform symptom reporting. A key source of somatosensory information is proprioception, yet the perception and integration of this sense has not been sufficiently investigated in those prone to somatoform disorders.